Moral disadvantages of cancelling the engagement and its amends (A comparative study between the Islamic jurisprudence and the Iraqi constitution) - Yassin, Kamal S. (Humanities Journal of University of Zakho, 2014)
The engagement initiates the marriage, it makes both fiancés know each other well and keep their relationship strong. Cancelling the engagement may occur sometimes even from the fiancé or the fiancée or her sponsor; that the engagement is not a marriage contract, but just a promise and in case of contract absence, there is no real relationship. This cancelling should be justified lawfully, if one of the fiancés found something wrong in his partner makes him reassess this relationship. A justified cancelling is necessary to preserve the social position for the fiancée.Iraqi constitution considers that the engagement is not a contract, it can be cancelled at any time without any justification, that engagement is just a social phenomenon which has no legal effect, and the reclaim of an emotional damage for the other side does not have a legal value for most judges. The permission of such type of claim might cause more damages because it open the door for more harmful accuses and scandals than the financial compensation demanded. If engagement cancelling accompanied with more harmful acts for one of the fiancés, we can ruling an equal compensation. On the other side, denying the moral disadvantage leads to more harmful damages on others reputation. These private and public disadvantages oblige us to think other solutions and we find that the judge is eligible to make the right amend.